Relationship between nickel exposure and the level of carcinoembryonic antigen among welders in an automotive plant - Chiang, Lee Juan; Mohd Tamrin, Shamsul Bahri; Ismail, Syazwan Aizat; Md Dan, Ridhuan; Sulaiman, Mohd Roslan; Hashim, Zailina (Science Publications, 2009)
Background: Study on the effect of nickel exposure in the occupational setting and its association to carcinoembryonic antigen (CEA) had been studied before. Questions were raised whether the result from previous study would also show the same pattern of the urinary nickel concentration in this study.